Artificial Intelligence and Customer Engagement in Driving Customer Satisfaction - Dhenisa Dewi Sulaeman; Hanna Nurhaliza; Siska Ernawati Fatimah (Universitas KH. Abdul Chalim Mojokerto, 2025)
To enhance user experience, online ojek applications have integrated Artificial Intelligence (AI) through features like chatbots, service recommendations, and interaction analysis. This study aims to examine the effect of AI implementation and customer engagement on customer satisfaction in the city of Cirebon. Using a quantitative approach with 401 respondents, data were collected through a questionnaire and analyzed using Slovin’s formula and Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that AI significantly improves customer satisfaction by increasing service accessibility and ease of use. Furthermore, AI positively influences customer engagement, which in turn has a substantial impact on overall customer satisfaction.